A New Decoupling Controller for Multi-Time Delayed TITO Processes - Nguyen, Thu Ha; Nguyen, Doan Phuoc (Old Journal, 2018)
Multiple-input-multiple-output systems (MIMO) are very popular in the industry, such as distillation column plant, liquid dispensers, infant incubators, quadruple tank... One of the difficulties to handle them is how to eliminate interactions between variables. The decoupling control is a research field related to solving this problem, which has been studied by many authors in the past. This paper addresses to propose a new decoupling control method applied for two input two output processes (TITO) with multi-time delays. Simulation results show that the performance of the system is improved in the sense, that no longer interfering between the loops is occurred as well as the process output disturbances had been completely eliminated.